Ambient Noise Analysis During Nyepi in Denpasar Using Horizontal-to-Vertical Spectral Ratio (HVSR) Method - I Putu Dedy Pratama; Dwi Karyadi Priyanto; Pande Komang Gede Arta Negara (Himpunan Ahli Geofisika Indonesia (HAGI), 2020)
Nyepi Day is a unique tradition where outdoor human activities stop 24 hours a day. Denpasar City is the region that has the most significant impact on this change because it is the capital province. This study aims to determine the effect of Nyepi on ambient noise in Denpasar on March 25, 2020. We installed a TDS sensor at the Denpasar Geophysics Station for 3x24 hours ie when Nyepi Day, before and after Nyepi as comparative data. The data is processed by the HVSR method to get the value of dominant frequency and amplification factor every hour. Compared to the day before and after Nyepi, the dominant frequency increased during Nyepi and the amplification factor decreased during Nyepi. Seismic vulnerability index value at Nyepi is 24 where there is a decrease of index 3,904 with a day before and after Nyepi. This is showed that Nyepi Day affected ambient noise in Denpasar.